2001
DOI: 10.1007/bf02234323
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy for adenocarcinoma of the rectum

Abstract: Neoadjuvant therapy for adenocarcinoma of the rectum is well tolerated and can produce substantial down-staging and a high curative resection rate. Chemoradiation can achieve high complete pathologic response rates, although toxicity during neoadjuvant therapy is greater than for radiation alone. Short-course radiation can achieve down-staging of both T stage and N stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 42 publications
2
51
1
2
Order By: Relevance
“…Preoperative radiotherapy is superior to the postoperative radiotherapy (Sauer et al, 2004). With the wide application of radiotherapy in rectal cancer, more and more studies have found clinical efficacy and adverse effects of radiotherapy showed significant individual difference (Read et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative radiotherapy is superior to the postoperative radiotherapy (Sauer et al, 2004). With the wide application of radiotherapy in rectal cancer, more and more studies have found clinical efficacy and adverse effects of radiotherapy showed significant individual difference (Read et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies demonstrated that the DS rates for unselected patients with rectal cancer treated with CRT was 45% (range, 40% to 60%), with a pCR rate of 8% to 14%. 2,7,8 By selecting a population likely to respond to standard CRT using TYMS genotyping, DS and ypT0 rates among patients with germline TSER *2/*2 or TSER *2/*3 were 64.4% and 20%, respectively. The DS rate was significantly better than the predicted DS rate of 45% (P ϭ .0001) and also higher than the 60% rate observed by Villafranca et al 27 in that particular subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The two-stage study design proposed by Simon 33 was used for sample size calculations for both groups: good-risk genotype (study 1) and poor-risk genotype (study 2). On the basis of both local and literature data, the DS rate for the general T3/T4 population was set at 45% with conventional therapy, 7,8,10,12 and the predicted DS rate for good-risk TYMS was 60%.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations